Anaphylaxis in a lactating infant who is allergic to cow’s milk protein - Ana Calle; Carlos Chinchilla; Ricardo Cardona (Revista Alergia México, 2019)
Background: Allergy to cow’s milk protein is a common problem in children. The clinical manifestations of the reactions that are mediated by IgE are varied and the anaphylactic reactions can be life-threatening.